Prevalence and Pattern of Accessory Teeth (Hyperdontia) in Permanent Dentition of Iranian Orthodontic Patients. - Fariborz Amini; Vahid Rakhshan; Sanaz Jamalzadeh (Tehran University of Medical Sciences, 2013)
Awareness of hyperdontia pattern/prevalence can be useful in early diagnosis and prevention by general practitioners, pediatric dentists, and orthodontists. Since the previous results regarding the pattern of hyperdontia (supernumerary teeth) are controversial, this study aimed to assess this subject among Iranian orthodontic patients.All approved panoramic radiographs of 3374 orthodontic patients (aged 10 to 20 years old) who had visited orthodontic departments of all Tehran dentistry universities and 10 private clinics during the years 1999-2009 were investigated to establish the prevalence/pattern of hyperdontia in permanent dentition (excluding third molars). The data were analyzed using a chi-square, a chi-square goodness-of-fit, and a Fisher exact test (α=0.05).Of the patients, 2012 were female and 1362 were male. The prevalence of hyperdontia was 0.72% (14 females [0.69% of females], 10 males [0.73% of males], female-to-male ratio=1:1.055). The difference between the genders was not significant (P = 0.896). No double or multiple supernumeraries were found. The most common accessory teeth were mesiodens (58.3%), maxillary laterals (25%), and maxillary premolars (16.7%). Hyperdontia was significantly more common (P=0.000) in maxilla (there was only one mandibular accessory tooth). It was more frequent in the anterior segment (P=0.000). However the occurrence was not significantly different between bimaxillary right and left quadrants (P=0.6).Hyperdontia was more common in premaxilla, and the most common accessory tooth was mesiodens. Unlike earlier studies, no bilateral accessory teeth were found. Also no gender dimorphism was discerned.